Students’ Perception in Using Commom European Framework of Reference (CEFR) Application as an English Laguage Learning Assessment - Yusak Runesi; Tinni Mogea; Nihta V. F. Liando (Peneliti.net, 2022)
This research focused on the Student Perception in Using Common European Framework of References (CEFR) Application as an English Learning Assessment and the benefit of it for the students in English language teaching at SMA Prisma Pioneer Manado. This research used a descriptive qualitative method, because it was intedeed to obtain information related to the Student Perception in Using Common European Framework of References (CEFR) application as an English Learning assessment. The subject of this research was all class students with the total number of partcipants 54 students in 2021/2022 academic year. The data of students’perception about using CEFR application obtained from the result of the questionnaire. The data were obtained through the questionnaire were analysed and tabulated based on the classification of perception using Likert scalet. The results of data analysis showed that (1) students’ perception was positive in using CEFR application as an English Language learning by mean score 84 (2) based on the students’ classification that (30%) students classified as Strongly Agree (positive), (55%) students classified as agree (positive),(12%) students classified as Disagree (negative),(3%) students classified as strongly disagree (strongly negative). This was indicated that most studentsof Manado Prisma school like using CEFR as an English language learning assesment